How Does the Horizontal Position of Pictures and Text Affect Product Evaluation? Based on Left and Right Position Effect - Huang, Zan; Du, Yingjue; Xu, Feifei; Hu, Chuming (Frontiers in Psychology, 2022)
Due to the untouchability of online shopping environment, image and text description, as two main ways of product information display, are important indicators for consumers to evaluate products. However, few studies have discussed the synergistic effects of image and text information on consumers. In the present study, in conjunction with the left-right position effect, we examine the expectation that horizontal placement of visual stimuli in different directions has a strong influence on consumers' product evaluation preferences. This implicit assumption is based on consumers' unconscious psychological need for closure when processing information. The authors conducted two experiments to investigate the relative effects of image information and text statements at different locations in online shopping pages on consumer product evaluations. The results show that: (1) when the evaluation object is a search product, compared with the display mode of left text - right image, the display mode of left image - right text plays a more significant role in consumer product evaluation. The results of experiential products were just the opposite. The way of presenting the text declaration on the left and image on the right has a stronger impact on consumers' evaluation preference for experiential products (Study 1 and 3). (2) The difference in consumers' evaluation mode of different presentation sequences based on product attributes is driven by their visual information processing fluency (Study 2). These preferences are robust, and it is worth noting that only the order of graphic presentation has no significant influence on consumer product evaluation preference.